Substance use profiles, sociodemographic and clinical characteristics of adults with psychiatric disorders in childhood and adolescence - Altun Varmış, Dilek (Journal of Dependence, 2025)
Objective: This study aimed to examine the socio-demographic and clinical characteristics, as well as the substance use profiles, of adults diagnosed with psychiatric disorders during childhood and adolescence. Method: The sample comprised patients treated at the Alcohol and Substance Addiction Treatment Center (AMATEM), who were diagnosed with Substance Use Disorder (SUD), had a history of Child Psychiatry and/or CEMATEM admission, and tested positive for at least one substance in their urine. Relevant patient data were accessed from hospital records. Results: The study included 537 patients, of whom 52.1% were male and 47.9% were female, with a mean age of 32.2±9.4 years (range: 18–65). Among childhood diagnoses, conduct disorder was the most common (61.6%), followed by Attention Deficit and Hyperactivity Disorder (ADHD) (7.1%). In adulthood, the most prevalent substance use disorder was multiple substance use disorder (40.2%), followed by cannabis (39.8%) and heroin use (12.3%). Childhood trauma was significantly associated with gender, marital status, educational level, suicide attempts, sleep disorders, and childhood psychiatric diagnoses. Conclusion: The findings indicate that conduct disorder is the most common childhood diagnosis among patients with SUD, with a high prevalence of childhood trauma and treatment discontinuation. These insights underscore the importance of early interventions to address psychiatric disorders and prevent substance use.